CONTROL OF THE STEEL DEOXIDATION PROCESS USING DETERMINATIONS OF OXYGEN ACTIVITY IN METAL - S. V. Terletski; A. V. Olenchenko; V. V. Pivtsaev (Литьë и металлургия, 2006)
The technology of deoxidation of steel at output out of blast-steel furnace with consequent casting at MNLZ of small size with open metal spray is worked out.